2021
DOI: 10.1093/eurjpc/zwab046
|View full text |Cite
|
Sign up to set email alerts
|

The role of the electrocardiographic phenotype in risk stratification for sudden cardiac death in childhood hypertrophic cardiomyopathy

Abstract: Aims The 12-lead electrocardiogram (ECG) is routinely performed in children with hypertrophic cardiomyopathy (HCM). An ECG risk score has been suggested as a useful tool for risk stratification, but this has not been independently validated. This aim of this study was to describe the ECG phenotype of childhood HCM in a large, international, multi-centre cohort and investigate its role in risk prediction for arrhythmic events. Methods and resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
0
26
1
Order By: Relevance
“…12 lead ECG Proposed 12 lead ECG features include; measures of LV hypertrophy (82) and abnormal repolarisation (83). An ECG risk score has been developed by Ostman-Smith et al (83) but this was shown to have only moderate discriminatory ability in an external validation study (84).…”
Section: Agementioning
confidence: 99%
“…12 lead ECG Proposed 12 lead ECG features include; measures of LV hypertrophy (82) and abnormal repolarisation (83). An ECG risk score has been developed by Ostman-Smith et al (83) but this was shown to have only moderate discriminatory ability in an external validation study (84).…”
Section: Agementioning
confidence: 99%
“…Consequently, improved screening techniques for detecting are strongly required in the clinical arena (28). Recently a large, multicenter study in childhood hypertrophic cardiomyopathy demonstrated that ECG abnormalities were common and varied, but none of them, either in isolation or in the ECG risk score, were associated with the 5-year sudden cardiac death risk (29). Potentially, other individual ECG parameters may improve the current risk prediction models.…”
Section: The Usefulness Of Ecg Nomogramsmentioning
confidence: 99%
“…Studies in the sub-set of the study population for HCMRisk-Kids with ECGs archived found a cut-off of >5 points only modestly predictive for a wider end-point of “freedom from major arrhythmia in the next five years” over a short follow-up of only 3.9 yrs. However, when the total ECG point-score was used, the study found a hazard ratio of 1.11 per point, higher than the hazard ratio for the LA Z-score of 1.03 in the same population [ 59 ]. A recent external validation of the ECG risk score cut-off >5 points in a tertiary centre childhood-HCM study group from Toronto, with a mean follow-up of 14.6 y, found a sensitivity of 95% and specificity of 56% for SCD in the first 5 years of follow-up [ 64 ].…”
Section: Electrocardiographic Phenotypementioning
confidence: 99%
“…A recent external validation of the ECG risk score cut-off >5 points in a tertiary centre childhood-HCM study group from Toronto, with a mean follow-up of 14.6 y, found a sensitivity of 95% and specificity of 56% for SCD in the first 5 years of follow-up [ 64 ]. All the above studies find very high negative predictive values for cut-off >5 points, between 97–100% [ 19 , 59 , 65 , 66 ]. QTC dispersion is an additional ECG feature that has been reported to have a significant correlation with SCD in childhood-HCM, with a hazard ratio of 1.6 per 20 ms increase [ 22 ], or a cut-off of 0.055 being associated with arrhythmic end-point [ 26 ].…”
Section: Electrocardiographic Phenotypementioning
confidence: 99%
See 1 more Smart Citation